Development of a scalable, high throughput, low energy consuming, rapid vaccine production device - Andraski, Andrew J., author; Quinn, Jason, advisor; Mizia, John, advisor; Goodrich, Raymond, committee member (Colorado State University. Libraries, 2022)
Producing vaccines rapidly and efficiently is an incredibly important task. To accomplish this, we are required to develop novel vaccine manufacturing methods and technologies. With the onset of the COVID-19 pandemic and the prolonged struggle to mitigate its spread and devastating impacts, an entirely new approach to making an inactivated, whole virus vaccine was pioneered by a team of researchers at Colorado State University's (CSU) Infectious Disease Research Center (IDRC). The novel method employs ultraviolet light and riboflavin (Vitamin B2) to inactivate the virus so that it is suitable for use as a vaccine candidate. The novel method has been coined the "SolaVAX" process, and the efficacy of a COVID-19 vaccine produced using the SolaVAX process was proven in an animal challenge study during pre-clinical testing. An existing pathogen reduction technology (PRT) called Mirasol PRT was capable of manufacturing small batches of vaccine material in the laboratory. The Mirasol PRT was developed for inactivating pathogen in blood products. The technology's batch processing design is not suitable for efficiently producing large quantities of vaccine material and meeting the needs for current and future pandemic preparedness. To safely and efficiently inactivate large volumes of pathogen for vaccine production, flow-through processing rather than batch processing is necessary. In a collaborative effort, a team of engineering researchers at CSU's Energy Institute developed a device called the VacciRAPTOR that is estimated to be capable of processing 71 liters of pathogen solution per hour. This processing rate equates to producing over 100,000 human COVID-19 vaccine doses per hour. The VacciRAPTOR uses 18 broadband UV lamps to illuminate and inactivate a flowing solution of whole virus. It has reliably and repeatably inactivated Zika virus during preliminary testing. In addition to using broadband UV lamps for pathogen inactivation, high intensity narrowband UV LEDs were also explored. Both broadband UV emission from lamps and narrowband UV emission from LEDs proved to effectively inactivate whole Zika virion. Since both broadband and narrowband UV light emission from lamps and LEDS effectively inactivated Zika virus during lab testing, a combined Life Cycle Assessment (LCA) and Technoeconomic Analysis (TEA) was performed to compare the differences in global warming potential (GWP) and economic impact as a result of utilizing UV lamps versus UV LEDs for illumination. The LCA results indicate that using UV lamps is 24x less impactful (5.7 g-CO2-eq per liter of treated virion solution produced) than using UV LEDs (136 g-CO2-eq per liter of treated virion solution produced) when considering use-phase GWP. The TEA results indicate that using UV lamps is 14x less expensive ($6,300) than using UV LEDs ($87,600) when considering overnight capital and lifetime use-phase energy consumption costs. Since the SolaVAX method and VacciRAPTOR technology utilize ultraviolet light and Vitamin B2 rather than hazardous chemicals such as Formalin, this technology can be integrated into production centers without requiring that the center to be capable of handling the toxic and environmentally hazardous materials that are often associated with vaccine production. The device is scalable, compact, and low energy consuming. Scalability, compact design, and chemical-free processing opens the potential to distribute vaccine production capabilities when and where it is needed throughout much of the world.
Keywords: inactivation; riboflavin; vaccine; rapid vaccine production; inactivated virus; riboflavin photochemistry